Relationship between Helicobacter pylori infection and gastric atrophy and the stages of the oesophageal inflammation, metaplasia, adenocarcinoma sequence: results from the FINBAR case–control study. Issue 6 (19th November 2007) - Anderson, L A; Murphy, S J; Johnston, B T; Watson, R G P; Ferguson, H R; Bamford, K B; Ghazy, A; McCarron, P; McGuigan, J; Reynolds, J V; Comber, H; Murray, L J
Abstract : Objective: A number of studies have shown an inverse association between infection with Helicobacter pylori and oesophageal adenocarcinoma (OAC). The mechanism of the apparent protection against OAC by H pylori infection and, in particular, the role of gastric atrophy is disputed. The relationship between all stages of the oesophageal inflammation, metaplasia, adenocarcinoma sequence and H pylori infection and gastric atrophy was explored. Methods: A case–control study involving 260 population controls, 227 OAC, 224 Barrett's oesophagus (BO) and 230 reflux oesophagitis (RO) patients recruited within Ireland was carried out. H pylori and CagA (cytotoxin-associated gene product A) infection was diagnosed serologically by western blot, and pepsinogen I and II levels were measured by enzyme immunoassay. Gastric atrophy was defined as a pepsinogen I/II ratio of <3. Results: H pylori seropositivity was inversely associated with OAC, BO and RO; adjusted ORs (95% CIs), 0.49 (0.31 to 0.76), 0.35 (0.22 to 0.56) and 0.42 (0.27 to 0.65), respectively. Gastric atrophy was uncommon (5.3% of all subjects), but was inversely associated with non-junctional OAC, BO and RO; adjusted ORs (95% CIs), 0.34 (0.10 to 1.24), 0.23 (0.05 to 0.96) and 0.27 (0.08 to 0.88), respectively. Inverse associations between H pylori and the disease states remained in gastric atrophy-negative patients. Conclusion: H pylori infection and gastric atrophy are associated with a reduced risk of OAC, BO and RO. While use of the pepsinogen I/II ratio as a marker for gastric atrophy has limitations, these data suggest that although gastric atrophy is involved it may not fully explain the inverse associations observed with H pylori infection.